TGM6 is a helminth secretory product that mimics TGF-β binding to TGFBR2 to antagonize signaling in fibroblasts - Stephen E. White; Tristin A. Schwartze; Ananya Mukundan; Christina Schoenherr; Shashi P. Singh; Maarten van Dinther; Kyle T. Cunningham; Madeleine P. J. White; Tiffany Campion; John Pritchard; Cynthia S. Hinck; Peter ten Dijke; et al. (Nature Communications)
Abstract TGM6 is a natural antagonist of mammalian TGF-β signaling produced by the murine helminth parasite Heligmosomoides polygyrus. It differs from the previously described agonist, TGM1 (TGF-β Mimic-1), in that it lacks domains 1/2 that bind TGFBR1. It nonetheless retains TGFBR2 binding through domain 3 and potently inhibits TGF-β signaling in fibroblasts and epithelial cells, but does not inhibit TGF-β signaling in T cells, consistent with divergent domains 4/5 and an altered co-receptor binding preference. The crystal structure of TGM6 bound to TGFBR2 reveals an interface remarkably similar to that of TGF-β with TGFBR2. Thus, TGM6 has adapted its structure to mimic TGF-β, while engaging a distinct co-receptor to direct antagonism to fibroblasts and epithelial cells. The co-expression of TGM6, along with immunosuppressive TGMs that activate the TGF-β pathway, may minimize fibrotic damage to the host as the parasite progresses through its life cycle from the intestinal lumen to submucosa and back again. The co-receptor-dependent targeting of TGFBR2 by the parasite provides a template for the development of therapies for targeting the cancer- and fibrosis-promoting activities of the TGF-βs in humans.